The phone booth at the edge of the world - Imai Messina, Laura (Manilla Press, 2020)
On a windy hill in Japan, in a garden overlooking the sea stands a disused phone box. For years, people have travelled to visit the phone box, to pick up the receiver and speak into the wind: to pass their messages to loved ones no longer with us. When Yui loses her mother and daughter in the tsunami, she is plunged into despair and wonders how she will ever carry on. One day she hears of the phone box, and decides to make her own pilgrimage there, to speak once more to the people she loved the most. But when you have lost everything, the right words can be the hardest thing to find . . . Then she meets Takeshi, a bereaved husband whose own daughter has stopped talking in the wake of their loss. What happens next will warm your heart, even when it feels as though it is breaking...